POTENSI DAUN MANGROVE (Rhizopora mucronata) SEBAGAI ANTIDIABETES - Usman Sain; Dinda Noor Sukma; Bena Septariama Simatupang (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Rhizopora mucronate is a typical mangrove plant that easly found on the coast of Muara Badak Beach, Kutai Kartanegara Regency, East Borneo, Indonesia. The purpose of this research is to know the activity of active compound from mangrove Rhizopora mucronate leaves that have the potencial as antidiabetic. Samples of R. mucronata mangrove leaves were taken at Muara Badak beach region. Leaf samples that have been dried, are extracted by maceration using methanol solvent and followed by a partition extraction process using n-hexane solvent. The methanol and n-hexane extracts from R.mucronata mangrove leaves were obtained, followed by phytochemical tests (alkaloid, flavonoid, steroid, terpenoid, phenolic compounds, tannin, and saponin) qualitatively. Then the antidiabetic activity was tested using an oral glucose tolerance test method. Phytochemical test results of methanol and n-hexane extracts of R.mucronata mangrove leaves are positive contained group compounds; alkaloids, flavonoids, tannins and phenolics. The percentage decrease in blood glucose levels of mice for positive control (Glibenclamide 0.05 mg / kgBB) was 21.81%, methanol extract for group III (dose 62.5 mg / kgBB) 67.86%, Group IV (dose 125 mg / kgBB) 58.74% and Group V (group V (dose 62.5 mg / kgBW) 67.86%, Group IV (dose 125 mg / kgBW) 58.74% and Group V (group V (dose 62.5 mg / kgBW) dose 250 mg / kg) 36.72%. Then the percentage decrease in blood glucose levels of mice for n-hexane extract; Positive control was 11.60%, Group III (dose 62.5 mg / kgBW) was 20.1%, Group IV (dose 125 mg / kgBW) 7.83% and Group V (dose 250 mg / kgBW) 42.7%. The methanol extract of R.mucronata mangrove leaves at a dose of 62.5 mg / kgBB has the best antidiabetic activity. Whereas n-hexane extract has the best antidiabetic activity at a dose of 250 mg / kgBW. Thus the methanol and n-hexane extract of Rhizopora mucronata mangrove leaves has the potential as an antidiabetic.